Hemorrhagic Shock - Gonzalez, Katherine W.; Desai, Amita A.; Dalton, Brian G.; Juang, David (Journal of Pediatric Intensive Care, 2015)
Hemorrhagic shock has been studied extensively in the adult population, but evidence is lacking in the pediatric population. Unlike adults, pediatric patients tolerate hypovolemia with less hypotension until they have reached significant blood volume loss. It is imperative they receive prompt intravenous access, crystalloid resuscitation, followed by blood product transfusion. A hemoglobin goal of 7 g/dL has been translated to the pediatric population without evidence of poor outcomes. Massive transfusion protocols involving a 1:1:1 ratio of red blood cells:fresh frozen plasma:platelets has been recommended although further evidence is needed. With the transfusion of multiple blood products, consideration must be taken into account for the side effects, including electrolyte imbalance and lung injury.
Keywords: shock; massive transfusion; pediatrics; hemorrhage